Influence of task instructions and stimuli on the neural network of face processing: An ALE meta-analysis. (June 2018) - Müller, Veronika I.; Höhner, Yvonne; Eickhoff, Simon B.
Abstract: Many neuroimaging studies have investigated the neural correlates of face processing. However, the location of face-preferential regions differs considerably between studies, possibly due to the use of different stimuli or tasks. By using Activation likelihood estimation meta-analyses, we aimed to a) delineate regions consistently involved in face processing and b) to assess the influence of stimuli and task on convergence of activation patterns. In total, we included 77 neuroimaging experiments in healthy subjects comparing face processing to a control condition. Results revealed a core face-processing network encompassing bilateral fusiform gyrus (FFG), inferior occipital (IOG) gyrus, superior temporal sulcus/middle temporal gyrus (STS/MTG), amygdala, inferior frontal junction (IFJ) and gyrus (IFG), left anterior insula as well as pre-supplementary motor area (pre-SMA). Furthermore, separate meta-analyses showed, that while significant convergence across all task and stimuli conditions was found in bilateral amygdala, right IOG, right mid-FFG, and right IFG, convergence in IFJ, STS/MTG, right posterior FFG, left FFG and pre-SMA differed between conditions. Thus, our results point to an occipito-frontal-amygdalae system that is involved regardless of stimulus and attention, whereas the remaining regions of the face-processing network are influenced by the task-dependent focus on specific facial characteristics as well as the type of stimuli processed.